People like us : - Craven, Miles (Macmillan, 2003)
"People like us" is useful for adult and young adult learners of English. The book is an intergrated skills course exploring cultural values and attitudes. There are three aims: to help readers find out about other culture, to helpyou find out more about your own culture and to help you enjo preacticing your English.